2021
DOI: 10.1155/2021/7055101
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Combined Score of Plasma Fibrinogen and Neutrophil-Lymphocyte Ratio in Patients with Spontaneous Intracerebral Hemorrhage

Abstract: Background. The combination of plasma fibrinogen and neutrophil to lymphocyte ratio (F-NLR) score is a novel inflammatory marker constituted by peripheral blood fibrinogen concentration and neutrophil to lymphocyte ratio. In the current study, we aim to explore the relationship between admission F-NLR score and intracerebral hemorrhage (ICH) and assess its prognostic predictive ability in ICH patients. Methods. The original cohort was consecutively recruited from August 2014 to September 2017, and the validati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, research on the prognostic significance of the F-NLR score in aSAH is limited. Yang et al ( 11 ) had revealed the usefulness of F-NLR scores in ICH, it was an independent risk factor for 3-month functional outcomes. Despite the difference in disease entity, similar result was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, research on the prognostic significance of the F-NLR score in aSAH is limited. Yang et al ( 11 ) had revealed the usefulness of F-NLR scores in ICH, it was an independent risk factor for 3-month functional outcomes. Despite the difference in disease entity, similar result was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fibrinogen and NLR were classified into high and low groups based on the optimal cutoff values according to the receiver operating characteristic (ROC) curves. F-NLR score was defined as follows: (1) score 0, low fibrinogen and low NLR; (2) score 1, low fibrinogen and high NLR or high fibrinogen and low NLR; and (3) score 2, high fibrinogen and high NLR ( 11 ). Patients were not treated with steroids and received 2.0 g of tranexamic acid intravenously every 12 h after blood sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Yang et al . 46 established F-NLR score with the combination of plasma fibrinogen and NLR, which could predict poor prognosis after ICH. Nevertheless, this score also depended on the cutoff values from a single center and the AUCs of 1-month mortality and 3-month poor outcome were both lower than the inflammatory score (0.809 vs. 0.883; 0.699 vs. 0.857).…”
Section: Discussionmentioning
confidence: 99%
“…After sICH, neutrophils are the earliest recruited cells in the central nervous system [12]. Neutrophils infiltrate the brain parenchyma, facilitate the hematoma resolution and release multiple inflammatory factors [13].…”
Section: Discussionmentioning
confidence: 99%